Quality formation of germination brown rice under microwave drying: from GABA content to color value - Peng, Sun; Caihua, Xu; Wudong, Chen; Jifu, Bi; Changsheng, Han; Tong, Tong; Chenghai, Liu; Feng, Xu ` (Emirates Journal of Food and Agriculture, 2021)
In order to improve the final quality of germination brown rice (GBR), the changes of GBR in Gamma-aminobutyric acid (GABA) and color are investigated under microwave drying conditions. Results indicate that Microwave drying process may improve GABA in GBR due to microwave volumetric heating inducing the glutamic acid decarboxylase (GAD) activity; and the dried GBR with golden appearance under the microwave intensity of 2.75 W/g and the apparent velocity of 2.50 m/s considering the drying efficiency and quality of dried GBR. In this study, microwave drying conditions not only improve the drying efficiency of GBR, but also improve the appearance and color of GBR after drying, reduce GABA degradation and control the generation of burst rate.